DINAMIKA EPIDEMIOLOGI: MENGUNGKAP INTERAKSI HOST, AGEN, DAN LINGKUNGAN DALAM MENGHADAPI ANCAMAN PENYAKIT GLOBAL - Noviari, Dewi; Agustina, Santi (Kirana Publisher, 2025)
Diseases, both infectious and non-communicable, result from complex interactions between the host, the disease agent, and the environment. The epidemiological triad model serves as a fundamental framework for understanding disease transmission, identifying risk factors, and developing more effective prevention and control strategies. This article explores how the interplay between host, agent, and environment contributes to disease epidemiology and its relevance to both infectious and non-infectious diseases. In infectious diseases, agents such as viruses, bacteria, and parasites rely on environmental conditions and host immunity to thrive. Environmental factors such as sanitation, climate, and population density play a crucial role in determining the rate of disease transmission. Conversely, in non-communicable diseases, the agents are not microorganisms but risk factors like unhealthy diets, stress, and exposure to harmful substances. Environmental aspects such as urbanization, air pollution, and socioeconomic conditions also influence the occurrence of chronic diseases. Understanding the host-agent-environment model is essential for formulating public health policies. Environmental-based approaches, health regulations, and evidence-based medical interventions are key to future disease control efforts. This study emphasizes the need for a more holistic and multidisciplinary approach to address the increasingly dynamic global health challenges.